Polarizer, polarizing plate, method of manufacturing polarizer, and method of manufacturing polarizing plate

JP2025022124APending Publication Date: 2025-02-14SUMITOMO CHEM CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023126407
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-02
Publication Date
2025-02-14

AI Technical Summary

Benefits of technology

【0011】 本発明の偏光子によれば、保護フィルムとの密着力を向上させることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025022124000001_ABST
    Figure 2025022124000001_ABST
Patent Text Reader

Abstract

To improve interlayer adhesion with a protective film.SOLUTION: A polarizer 11 comprising a polyvinyl alcohol resin film containing a dichroic pigment adsorbed and aligned therein is provided, the polarizer featuring a boric acid cross-linking degree of 3.3 or less, a visibility-corrected single transmittance of 40% or greater, and a visibility corrected polarization degree of 99.98 or greater.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polarizer, a polarizing plate, a method for manufacturing a polarizer, and a method for manufacturing a polarizing plate. [Background technology]

[0002] A polarizer in which a dichroic dye is adsorbed and aligned on a polyvinyl alcohol-based resin film is known. Patent Document 1 describes that, although high optical properties can be obtained by increasing the degree of boric acid crosslinking of the polarizer, shrinkage due to temperature change is likely to occur. It describes a manufacturing method for a polarizing film that is unlikely to shrink due to temperature change while increasing the degree of boric acid crosslinking. It also describes that a protective film is attached to one or both sides of the polarizer using an adhesive or the like to be used as a polarizing plate. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2022-136978 A Summary of the Invention [Problem to be solved by the invention]

[0004] In a polarizer in which a dichroic dye is adsorbed and oriented in a polyvinyl alcohol-based resin film, there is a demand for further improvement in adhesion to a protective film. [Means for solving the problem]

[0005] The present invention includes the following inventions. [Invention 1] A polarizer in which a dichroic dye is adsorbed and oriented on a polyvinyl alcohol-based resin film, The degree of boric acid crosslinking is 3.3 or less, The visibility-corrected single transmittance is 40% or more, A polarizer with a luminous efficiency corrected polarization degree of 99.98% or more.

[0006] [Invention 2] A polarizing plate comprising the polarizer according to [Invention 1] and a protective film on at least one surface of the polarizer.

[0007] [Invention 3] Further, the polarizer has an attachment layer for attaching the polarizer to the protective film, The polarizing plate according to [Invention 2], wherein the attachment layer is a layer formed by curing an active energy ray-curable adhesive.

[0008] [Invention 4] A method for producing a polarizer in which a dichroic dye is adsorbed and oriented on a polyvinyl alcohol-based resin film, comprising the steps of: A dyeing step of dyeing the polyvinyl alcohol-based resin film with a dichroic dye; a crosslinking step of crosslinking the polyvinyl alcohol-based resin film that has been subjected to the dyeing step; A drying step of drying the polyvinyl alcohol-based resin film that has been subjected to the crosslinking step, The crosslinking step includes a first crosslinking step of immersing a polyvinyl alcohol-based resin film in a first crosslinking bath having a boric acid content of 4.0 parts by mass or less per 100 parts by mass of water; a second crosslinking step of immersing the polyvinyl alcohol-based resin film that has been subjected to the first crosslinking step in a second crosslinking bath having a boric acid content of 3.5 parts by mass or less per 100 parts by mass of water.

[0009] [Invention 5] The method for producing a polarizer according to [Invention 4], wherein the temperature of the first crosslinking bath is 60° C. or lower, and the temperature of the second crosslinking bath is 45° C. or lower.

[0010] [Invention 6] A step of producing a polarizer by the production method according to [Invention 4] or [Invention 5]; and a lamination step of laminating a protective film to one or both surfaces of the polarizer via an adhesive layer. Effect of the Invention

[0011] According to the polarizer of the present invention, the adhesion to the protective film can be improved. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a schematic cross-sectional view showing a polarizing plate of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view that illustrates an example of a polarizer manufacturing method and a polarizer manufacturing apparatus used in the method according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, the embodiments of the present invention will be described in detail. Note that the scope of the present invention is not limited to the embodiments described here, and various modifications can be made without departing from the spirit of the present invention.

[0014] <Polarizer> The polarizer 11 is a polyvinyl alcohol-based resin film in which a dichroic dye is adsorbed and aligned. As the polyvinyl alcohol-based resin, for example, a saponified polyvinyl acetate-based resin can be used. The saponification degree of the polyvinyl acetate-based resin is preferably 85 mol% or more, more preferably 90 mol% or more, and even more preferably 99 mol% or more.

[0015] Examples of polyvinyl acetate resins that can be used include polyvinyl acetate, which is a homopolymer of vinyl acetate, and copolymers of vinyl acetate with other monomers that can be copolymerized with vinyl acetate, etc. Examples of the other copolymerizable monomers include unsaturated carboxylic acids, olefins, vinyl ethers, and unsaturated sulfonic acids.

[0016] The degree of polymerization of the polyvinyl alcohol resin is preferably 1,000 or more and 10,000 or less, and more preferably 1,500 or more and 5,000 or less. The polyvinyl alcohol resin may be modified. Examples of the modified polyvinyl alcohol resin include polyvinyl formal, polyvinyl acetal, polyvinyl butyral, and the like, which are modified with aldehydes.

[0017] Examples of the dichroic dye include iodine and water-soluble dichroic dyes. The thickness of the polarizer 11 is not particularly limited, but is 1 μm or more, preferably 5 μm or more, more preferably 10 μm or more, and further preferably 20 μm or more, and is 50 μm or less, preferably 30 μm or less.

[0018] The polarizer 11 has a boric acid crosslinking degree of 3.3 or less, and preferably 3.2 or less. From the viewpoint of improving the polarization degree, the boric acid crosslinking degree is 2.5 or more, preferably 2.8 or more, and more preferably 3.0 or more.

[0019] In the polarizer 11 of the present embodiment, a dichroic dye is adsorbed and aligned on a polyvinyl alcohol-based resin film, and the degree of boric acid crosslinking is 3.3 or less. When the degree of boric acid crosslinking is 3.3 or less, the number of sites where the hydroxyl groups of the polyvinyl alcohol-based resin are crosslinked with boric acid is relatively small. In other words, the amount of hydroxyl groups not crosslinked with boric acid in the polyvinyl alcohol-based resin is relatively large. Therefore, as shown in FIG. 1, when the polarizer 11 and the protective film 13 are bonded together via an adhesive, the interaction between the hydroxyl groups of the polyvinyl alcohol-based resin and the adhesive can be increased. This can improve the adhesion between the polarizer 11 and the adhesive layer 12, and therefore the adhesion between the polarizer 11 and the protective film 13 can be improved.

[0020] The luminosity-corrected single transmittance is 40% or more, preferably 41% or more, more preferably 42% or more, and further preferably 43% or more. The luminosity-corrected polarization degree is 99.9% or more, preferably 99.95% or more, and more preferably 99.98% or more.

[0021] The methods for measuring the degree of boric acid crosslinking, the luminous efficiency-corrected single transmittance, and the luminous efficiency-corrected polarization degree will be described later. <Polarizing plate> 1, a polarizing plate 10 can be obtained by bonding a protective film 13 via an adhesive to at least one surface of a polarizer 11. That is, the polarizing plate 10 has a polarizer 11, a protective film 13, and an adhesive layer 12 that bonds the polarizer 11 and the protective film 13 together.

[0022] As the protective film 13, a known transparent protective film can be used. Specific examples of the protective film 13 include acetylcellulose-based resin films such as triacetylcellulose and diacetylcellulose, polyester-based resin films such as polyethylene terephthalate, polyethylene naphthalate, and polybutylene terephthalate, polycarbonate-based resin films, cycloolefin-based resin films, acrylic-based resin films, and chain olefin-based resin films such as polypropylene-based resins.

[0023] The thickness of the protective film 13 is not particularly limited, but is 1 μm or more, preferably 10 μm or more, and more preferably 30 μm or more, from the viewpoint of handling in the manufacturing process, and is 200 μm or less, preferably 100 μm or less, more preferably 80 μm or less, and even more preferably 60 μm or less, from the viewpoint of thinning the polarizing plate.

[0024] Examples of the adhesive used to bond the polarizer 11 and the protective film 13 include an active energy ray-curable adhesive such as an ultraviolet ray-curable adhesive, an aqueous solution of a polyvinyl alcohol-based resin or an aqueous solution containing a crosslinking agent, and a water-based adhesive such as a urethane-based emulsion adhesive.

[0025] Among these, an active energy ray-curable adhesive is preferable. In other words, the adhesive layer 12 of the polarizing plate 10 is preferably a layer formed by curing an active energy ray-curable adhesive.

[0026] The active energy ray curable adhesive is an adhesive that is cured by irradiation with active energy rays such as ultraviolet rays, visible light, X-rays, or electron beams. The active energy ray curable adhesive has adhesiveness even before irradiation with active energy rays, and therefore can be easily adhered to the surface of the polarizer 11 or the protective film 13. In addition, the adhesive strength can be adjusted by the amount of irradiation with active energy rays.

[0027] The thickness of the adhesive layer 12 is not particularly limited, but is 0.01 μm or more, preferably 0.1 μm or more, more preferably 0.5 μm or more, and even more preferably 1 μm or more. Also, it is 10 μm or less, preferably 5 μm or less, and more preferably 3 μm or less. When an active energy ray curable adhesive is used as the adhesive, the thickness of the adhesive layer 12 refers to the thickness of the layer in which the active energy ray curable adhesive is cured.

[0028] In order to improve the adhesion between the polarizer 11 and the protective film 13, a surface treatment may be applied to the bonding surface of at least one of the polarizer 11 and the protective film 13. Examples of the surface treatment include corona treatment, flame treatment, plasma treatment, ultraviolet irradiation, primer coating treatment, and saponification treatment.

[0029] <Method of manufacturing polarizer> As shown in Fig. 2, the polarizer 11 is manufactured using a polarizer manufacturing apparatus 20. The polarizer manufacturing apparatus 20 has a treatment bath containing a treatment liquid. Specifically, the polarizer manufacturing apparatus 20 has a swelling bath 14, a dyeing bath 15, a first crosslinking bath 16a, a second crosslinking bath 16b, a complementary color bath 17, and a cleaning bath 18. The polarizer manufacturing apparatus 20 also has a drying furnace 19, guide rolls 30-52, 60, and 61, and nip rolls 70-77.

[0030] When manufacturing the polarizer 11, an unstretched raw film 21, which is a raw sheet of polyvinyl alcohol resin, is used. The raw film 21 is wound around a roll 22. First, the raw film 21 is unwound from the roll 22 and transported along the film transport path of the polarizer manufacturing apparatus 20. Next, a treatment step is performed in which the raw film 21 is immersed in a treatment bath containing a treatment liquid and then pulled out. Furthermore, a drying step is performed, whereby a long polarizer 11 can be continuously manufactured. Note that the arrow in FIG. 2 indicates the transport direction of the film. The treatment bath is also referred to as a treatment tank.

[0031] Examples of the treatment liquid include a swelling liquid, a dyeing liquid, a first crosslinking liquid, a second crosslinking liquid, a color complementing liquid, and a cleaning liquid. The swelling process refers to a process in which a swelling liquid is brought into contact with the original film 21 to perform a swelling process. The dyeing process refers to a process in which a dyeing liquid is brought into contact with the film after the swelling process to perform a dyeing process. The first crosslinking process refers to a process in which a first crosslinking liquid is brought into contact with the film after the dyeing process to perform a first crosslinking process. The second crosslinking process refers to a process in which a second crosslinking liquid is brought into contact with the film after the first crosslinking process to perform a second crosslinking process. The complementary color process refers to a process in which a complementary color liquid is brought into contact with the film after the second crosslinking process to perform a complementary color process. The cleaning process refers to a process in which a cleaning liquid is brought into contact with the film after the complementary color process to perform a cleaning process.

[0032] The guide rolls 30-52, 60, and 61 are used to support the transported film and change the transport direction of the film. The nip rolls 70-77 are used to press and pinch the transported film and apply a driving force to the film by rotating. Furthermore, by arranging the nip rolls 70-77 before and after each treatment bath, a peripheral speed difference can be created between the nip rolls 70-77 arranged before and after each treatment bath in one or more treatment baths. By creating a peripheral speed difference between the nip rolls 70-77, it becomes possible to perform inter-roll stretching. That is, a uniaxial stretching process can be performed as a stretching process between a series of treatment processes.

[0033] The polarizer production apparatus 20 transports the film using guide rolls 30 to 52, 60, and 61 and nip rolls 70 to 77. The film then passes through a swelling bath 14, a dyeing bath 15, a first crosslinking bath 16a, a second crosslinking bath 16b, a complementary color bath 17, and a cleaning bath 18, which are provided on the film transport path, in that order. Finally, the film passes through a drying oven 19.

[0034] The guide rolls 30-52, 60, 61 and the nip rolls 70-77 can be disposed before, after, or within each treatment bath. This allows the film to be efficiently introduced into and immersed in the treatment bath, and removed from the treatment bath. For example, by providing one or more guide rolls in each treatment bath and transporting the film along these guide rolls, the film can be efficiently immersed in each treatment bath.

[0035] Each processing step will be described in detail below. (Swelling process) The swelling step is a step in which the raw film 21 is brought into contact with a swelling liquid to perform a swelling treatment.

[0036] In the swelling step, it is also possible to remove foreign matter from the surface of the raw film 21, remove plasticizers in the raw film 21, impart easy dyeability, plasticize the raw film 21, and the like. The treatment conditions are determined within a range that does not cause defects such as excessive dissolution or devitrification of the raw film 21.

[0037] 2, the swelling step is performed by transporting the original film 21 along a film transport path while continuously unwinding it from a roll 22. Furthermore, the original film 21 is immersed in a swelling bath 14 for a predetermined time and then pulled out.

[0038] 2, from when the original film 21 is unwound until when it is immersed in the swelling bath 14, the original film 21 is transported along a film transport path formed by guide rolls 60, 61 and a nip roll 70. During the swelling treatment, the original film 21 is transported along a film transport path formed by guide rolls 30 to 32 and a nip roll 71.

[0039] Pure water can be used as the swelling liquid of the swelling bath 14. Also usable are aqueous solutions of boric acid (JP Patent Publication No. 10-153709), chlorides (JP Patent Publication No. 06-281816), inorganic acids, inorganic salts, water-soluble organic solvents, alcohols, etc. The concentration in the aqueous solution can be in the range of 0.01% by mass to 10% by weight.

[0040] The temperature of the swelling bath 14 is, for example, 10° C. or higher, and preferably 20° C. or higher, and 50° C. or lower, and preferably 40° C. or lower. The immersion time of the raw film 21 is 10 seconds or more, preferably 20 seconds or more, and 300 seconds or less, preferably 200 seconds or less.

[0041] In the swelling process, the raw film 21 may swell in the width direction, causing wrinkles in the film. As a means for conveying the film while removing the wrinkles, rolls having a width expanding function, such as expander rolls, spiral rolls, and crown rolls, may be used for the guide rolls 30 to 32. Other width expanding devices, such as cross guiders, bend bars, and tenter clips, may also be used.

[0042] Another method for suppressing the occurrence of wrinkles is to perform a stretching process. For example, a uniaxial stretching process may be performed in the swelling bath 14 by utilizing the difference in peripheral speed between the nip rolls 70 and 71. These methods are collectively referred to as "means for suppressing wrinkles."

[0043] During the swelling treatment, the original film 21 also swells and expands in the transport direction of the film. When the original film 21 is not actively stretched, it is preferable to suppress sagging of the original film 21 in the transport direction. For example, it is preferable to take measures such as controlling the speed of the nip rolls 70, 71 arranged before and after the swelling bath 14. It is also preferable to stabilize the transport of the film in the swelling bath 14. For example, it is useful to control the water flow in the swelling bath 14 with an underwater shower or to use an EPC device (Edge Position Control device: a device that detects the edge of the film and prevents the film from meandering) in combination.

[0044] As shown in FIG. 2, the film pulled out from the swelling bath 14 passes through a guide roll 32, a nip roll 71 and a guide roll 33 in this order, and is introduced into a dye bath 15. (dying process) The dyeing step is a step of bringing the swelling-treated film into contact with a dyeing solution to perform dyeing treatment. Specifically, in the dyeing step, a dichroic dye is adsorbed and oriented on the swelling-treated polyvinyl alcohol-based resin film.

[0045] 2, in the dyeing step, the swelling treated film is transported along a film transport path formed by a nip roll 71, guide rolls 33 to 36, and a nip roll 72. The film is then immersed in a dye bath 15 for a predetermined time and then pulled out.

[0046] In order to improve the dyeability of the dichroic dye, the film to be subjected to the dyeing step is preferably a film that has been subjected to at least some degree of uniaxial stretching treatment. Alternatively, instead of or in addition to the uniaxial stretching treatment before the dyeing treatment, it is preferable to perform a uniaxial stretching treatment during the dyeing treatment.

[0047] As the dichroic dye, for example, iodine can be used. When iodine is used as the dichroic dye, the dyeing solution of the dye bath 15 can be, for example, an aqueous solution having a mass ratio of iodine / potassium iodide / water=0.003-0.3 / 0.1-20 / 100.

[0048] Instead of potassium iodide, other iodides such as zinc iodide may be used, or potassium iodide may be used in combination with other iodides. In addition, compounds other than iodides, such as boric acid, zinc chloride, cobalt chloride, etc. may be allowed to coexist.

[0049] When boric acid is added, it is distinguished from the crosslinking treatment described below in that it contains iodine. If the aqueous solution contains 0.003 parts by mass or more of iodine per 100 parts by mass of water, it can be considered as a dye bath 15.

[0050] The temperature of the dye bath 15 when the film is immersed is 10° C. or higher, preferably 20° C. or higher, and 50° C. or lower, preferably 40° C. or lower. The immersion time of the film is 10 seconds or more, preferably 30 seconds or more, and 600 seconds or less, preferably 300 seconds or less.

[0051] In the dyeing process, the film may be uniaxially stretched and wrinkle-preventing measures may be taken. In the example shown in FIG. 2, the film drawn out from the dye bath 15 passes through a guide roll 36, a nip roll 72, and a guide roll 37 in this order, and is introduced into the first crosslinking bath 16a.

[0052] (Crosslinking process) The crosslinking step is a step in which a crosslinking treatment is carried out by bringing a crosslinking liquid into contact with the dyed film. One of the purposes of the crosslinking step is to make the film water-resistant through crosslinking.

[0053] The cross-linking step includes a first cross-linking step and a second cross-linking step. (1st crosslinking step) 2, in the first crosslinking step, the dyed film is transported along a film transport path formed by a nip roll 72, guide rolls 37 to 40, and a nip roll 73. The film is then immersed in a first crosslinking bath 16a for a predetermined time and then pulled out.

[0054] The first crosslinking bath 16a may be a solution in which a crosslinking agent is dissolved in a solvent. A boron compound is used as the crosslinking agent. A specific example of the boron compound is boric acid. In addition to boric acid, the boron compound may contain borax. In addition to boric acid, a compound other than the boron compound may be contained. Examples of the compound other than the boron compound include glyoxal and glutaraldehyde. These may be used alone or in combination of two or more.

[0055] The first crosslinking liquid contains 4.0 parts by mass or less, preferably 3.7 parts by mass or less, more preferably 3.5 parts by mass or less, and even more preferably 3.3 parts by mass or less of boric acid per 100 parts by mass of water. The first crosslinking liquid contains 1 part by mass or more, preferably 1.5 parts by mass or more of boric acid per 100 parts by mass of water.

[0056] When the dichroic dye used in the dyeing process is iodine, the first crosslinking liquid preferably contains an iodide in addition to boric acid. The amount of the iodide can be, for example, 1 part by mass or more and 20 parts by mass or less per 100 parts by mass of water.

[0057] Examples of iodides include potassium iodide, zinc iodide, etc. Compounds other than iodides, such as zinc chloride, cobalt chloride, zirconium chloride, sodium thiosulfate, potassium sulfite, and sodium sulfate, may also be present.

[0058] In the first crosslinking step, the concentrations of boric acid and iodide in the first crosslinking liquid and the temperature of the first crosslinking bath 16a can be appropriately selected. The first crosslinking liquid can be, for example, an aqueous solution having a mass ratio of boric acid / potassium iodide / water=1-4.0 / 1-20 / 100.

[0059] The temperature of the first crosslinking bath 16a when the film is immersed is 40° C. or higher, preferably 50° C. or higher, and 70° C. or lower, preferably 60° C. or lower, more preferably 58° C. or lower.

[0060] The immersion time of the film is 10 seconds or more, preferably 20 seconds or more, and more preferably 30 seconds or more, and is 600 seconds or less, preferably 300 seconds or less, more preferably 100 seconds or less, and even more preferably 50 seconds or less.

[0061] (Second crosslinking step) 2, the second crosslinking step is performed by transporting the film after the first crosslinking treatment along a film transport path formed by nip roll 73, guide rolls 41 to 44, and nip roll 74. The film is then immersed in second crosslinking bath 16b for a predetermined time and then pulled out.

[0062] The second crosslinking liquid contains 3.5 parts by mass or less of boric acid per 100 parts by mass of water, preferably 3.0 parts by mass or less, more preferably 2.8 parts by mass or less, and even more preferably 2.5 parts by mass or less. The second crosslinking liquid contains 1 part by mass or more of boric acid per 100 parts by mass of water, preferably 1.5 parts by mass or more.

[0063] From the viewpoint of adjusting the degree of crosslinking of the polarizer within the above range, the second crosslinking liquid preferably has a smaller content of boric acid per 100 parts by mass of water than the first crosslinking liquid. In the second crosslinking step, the concentrations of boric acid and iodide in the second crosslinking liquid and the temperature of the second crosslinking bath 16b can be appropriately selected.

[0064] The second crosslinking liquid can be, for example, an aqueous solution having a mass ratio of boric acid / potassium iodide / water=1-3.5 / 1-20 / 100. The temperature of the second crosslinking bath 16b when the film is immersed is 20° C. or higher, preferably 30° C. or higher, and 60° C. or lower, preferably 50° C. or lower, and more preferably 45° C. or lower.

[0065] The temperature of the second crosslinking bath 16b when the film is immersed is preferably lower than the temperature of the first crosslinking bath 16a, from the viewpoint of increasing the neck-in of the film and consequently improving the degree of polarization.

[0066] The immersion time of the film is 1 second or more, and from the viewpoint of adjusting the degree of crosslinking of the polarizer within the above range, is 30 seconds or less, preferably 20 seconds or less, and more preferably 10 seconds or less.

[0067] The immersion time of the film is preferably the same as or shorter than that of the first crosslinking step, for example, 25 seconds or more shorter than that of the first crosslinking step. In the first crosslinking step and the second crosslinking step, the film may be uniaxially stretched. In addition, measures to prevent wrinkles may be taken.

[0068] As shown in FIG. 2, the film pulled out from the second crosslinking bath 16 b passes through a guide roll 44 , a nip roll 74 and a guide roll 45 in this order, and is introduced into the complementary color bath 17 . (complementary color process) The complementary color process is a process in which a complementary color liquid is brought into contact with the film after the second crosslinking process to perform complementary color processing. One of the purposes of the complementary color process is to adjust the hue.

[0069] 2, the color-complementing step is performed by transporting the film after the second crosslinking treatment along a film transport path formed by nip roll 74, guide rolls 45 to 48, and nip roll 75. The film is then immersed in color-complementing bath 17 for a predetermined time and then pulled out.

[0070] The complementary liquid may be a solution in which a crosslinking agent is dissolved in a solvent, as in the crosslinking liquid. Examples of the crosslinking agent include boron compounds, glyoxal, and glutaraldehyde. Examples of the boron compounds include boric acid and borax. These may be used alone or in combination of two or more. Examples of the solvent may include water, but may also include an organic solvent compatible with water.

[0071] The complementary color liquid may be, for example, an aqueous solution containing 1 to 3 parts by mass of a boron compound such as boric acid per 100 parts by mass of water. It is preferable to use an aqueous solution containing 1.5 to 3 parts by mass. When the dichroic dye used in the dyeing process is iodine, the complementary color liquid preferably contains iodide in addition to boric acid.

[0072] The amount of iodide can be, for example, 1 part by mass or more and 20 parts by mass or less per 100 parts by mass of water. Examples of iodides include potassium iodide, zinc iodide, etc. Compounds other than iodides, such as zinc chloride, cobalt chloride, zirconium chloride, sodium thiosulfate, potassium sulfite, and sodium sulfate, may also be present.

[0073] In the complementary color treatment, the concentrations of boric acid and iodide in the complementary color liquid and the temperature of the complementary color bath 17 can be appropriately selected. The complementary color liquid may be, for example, an aqueous solution having a mass ratio of boric acid / potassium iodide / water=1-3.5 / 1-20 / 100.

[0074] The temperature of the complementary color bath 17 when the film is immersed is 20° C. or higher, preferably 30° C. or higher, and 60° C. or lower, preferably 50° C. or lower, and more preferably 45° C. or lower.

[0075] The immersion time of the film is 1 second or more, and 30 seconds or less, preferably 20 seconds or less, and more preferably 10 seconds or less. The crosslinking treatment and the complementary color treatment may be carried out multiple times, usually 2 to 5 times. In this case, the composition and temperature of each crosslinking bath and each complementary color bath used may be the same or different.

[0076] In the color complementing step, the film may be uniaxially stretched, and wrinkles may be prevented. In the example shown in FIG. 2, the film withdrawn from the complement bath 17 passes through a guide roll 48, a nip roll 75 and a guide roll 49 in this order before being introduced into the washing bath 18.

[0077] (Cleaning process) The cleaning process is a process in which the film after the color complementation process is brought into contact with a cleaning solution to perform a cleaning process. The cleaning process is performed for the purpose of removing excess chemicals such as boric acid and iodine that are attached to the polyvinyl alcohol-based resin film.

[0078] 2, the cleaning step is performed by transporting the film after the complementary color processing along a film transport path formed by nip roll 75, guide rolls 49 to 52, and nip roll 76. The film is then immersed in cleaning bath 18 for a predetermined time and then pulled out.

[0079] The cleaning liquid used in the cleaning step may be water such as pure water. The cleaning step can also be carried out by spraying the cleaning liquid as a shower onto the film instead of immersing the film in the cleaning bath 18, or by combining immersion in the cleaning bath 18 with spraying of the cleaning liquid.

[0080] The temperature of the washing bath 18 in the washing treatment is preferably 2° C. or more and 40° C. or less, and the immersion time of the film is preferably 1 second or more and 120 seconds or less. During the washing step, the film can be uniaxially stretched and wrinkle-preventing measures can be taken.

[0081] In the example shown in FIG. 2, the film withdrawn from the cleaning bath 18 passes through a guide roll 52 and a nip roll 76 in that order, and is introduced into a drying oven 19 . (Stretching process) As described above, the raw film 21 is uniaxially stretched in a wet or dry manner during the series of processing steps, that is, before, after, or during one or more of the processing steps.

[0082] As a specific method of the uniaxial stretching treatment, for example, roll-to-roll stretching can be adopted, in which a difference in peripheral speed is applied between two nip rolls constituting a film transport path, for example, two nip rolls arranged before and after a treatment bath, to perform longitudinal uniaxial stretching. Alternatively, hot roll stretching, tenter stretching, etc. as described in Japanese Patent No. 2731813 can be adopted. Among these, roll-to-roll stretching is preferred.

[0083] The uniaxial stretching step can be carried out multiple times until a polarizing film is obtained from the raw film 21. As described above, the stretching treatment is also advantageous in preventing the occurrence of wrinkles in the film.

[0084] The final cumulative stretch ratio of the polarizing film based on the original film 21 is preferably 4.5 to 7 times, more preferably 5 to 6.5 times. The stretching step may be performed in any of the processing steps, and even when the stretching treatment is performed in two or more processing steps, the stretching treatment may be performed in any of the processing steps.

[0085] (drying process) After the washing step, it is preferable to carry out a treatment for drying the polyvinyl alcohol-based resin film.

[0086] 2, although there is no particular limitation on the method for drying the film, it is preferable to use a drying oven 19. The drying oven 19 may be, for example, one equipped with a hot air dryer.

[0087] The drying temperature is, for example, 30° C. or higher, preferably 50° C. or higher, more preferably 60° C. or higher, and even more preferably 70° C. or higher. Also, it is 100° C. or lower, preferably 90° C. or lower, and more preferably 80° C. or lower.

[0088] The drying time is, for example, 30 seconds or more, preferably 50 seconds or more, and more preferably 80 seconds or more. Also, it is 600 seconds or less, preferably 300 seconds or less, and more preferably 200 seconds or less. The treatment for drying the polyvinyl alcohol-based resin film can also be performed using a far-infrared heater.

[0089] The obtained polarizer 11 may be wound up on a winding roll to form a roll, or may be directly subjected to a polarizing plate production step, i.e., a step of laminating a protective film or the like on one or both sides of the polarizer, without being wound up.

[0090] <Method of manufacturing polarizing plate> The method for producing the polarizing plate 10 includes a step of producing the polarizer 11 by the above-mentioned method, and a laminating step of laminating the protective film 13 to one or both sides of the obtained polarizer 11 via an adhesive layer.

[0091] As shown in FIG. 1, in the laminating step, it is preferable to form an adhesive layer 12 using an active energy ray curable adhesive (hereinafter, also simply referred to as "adhesive"). In the lamination step, an adhesive is applied onto the protective film 13. The adhesive can be applied, for example, using a known bar coater. The thickness of the adhesive after application is not particularly limited, and can be, for example, 0.1 μm or more and 10 μm or less.

[0092] Next, the polarizer 11 is attached to the adhesive-coated surface of the protective film 13. The polarizer 11 can be attached by using, for example, a nip roll. The surface of the polarizer 11 may be previously subjected to a surface treatment such as a corona treatment.

[0093] Next, ultraviolet light is irradiated from the protective film 13 side to polymerize and harden the adhesive. By the above procedure, a polarizing plate 10 can be obtained in which a protective film 13 is attached to one or both sides of a polarizer 11 via an adhesive layer 12 .

[0094] 2, the method for producing a polarizer 11 of this embodiment includes a first crosslinking step and a second crosslinking step as crosslinking steps. The first crosslinking step uses a first crosslinking bath 16a containing 4.0 parts by mass or less of boric acid relative to 100 parts by mass of water. The second crosslinking step uses a second crosslinking bath 16b containing 3.5 parts by mass or less of boric acid relative to 100 parts by mass of water.

[0095] In both the first crosslinking step and the second crosslinking step, a crosslinking bath with a relatively small content of boric acid is used. Therefore, according to the manufacturing method of the polarizer 11 of the present embodiment, it is easy to manufacture the polarizer 11 having a boric acid crosslinking degree of 3.3 or less. In addition, since the second crosslinking bath 16b has a smaller content of boric acid than the first crosslinking bath 16a, the polarizer 11 having a boric acid crosslinking degree of 3.3 or less can be efficiently manufactured.

[0096] Furthermore, by setting the temperature of the first crosslinking bath to 60° C. or less and the temperature of the second crosslinking bath to 45° C. or less, a polarizer having a degree of boric acid crosslinking of 3.3 or less can be produced more efficiently. EXAMPLES

[0097] The present invention will now be described in more detail with reference to examples. In the examples, "%" and "parts" refer to % by mass and parts by mass unless otherwise specified. <Measurement and evaluation methods> (1) Thickness of polarizer With respect to the polarizers obtained in each of the Examples and Comparative Examples, the thickness was measured using a digital micrometer MH-15M manufactured by Nikon Corporation.

[0098] (2) Degree of crosslinking For each of the polarizers obtained in the Examples and Comparative Examples, a measurement sample was cut out from the center to a size of 10 cm x 10 cm. The crosslinking degree of this sample was measured using an Agilent Technologies Cary660 (FT-IR) device.

[0099] A diamond crystal of Specac Golden Gate (ATR) was used, the number of scans was 16, and the resolution was 2 cm -1 So I went. In addition, the IR data measured at 2500 cm -1 More than 3700cm -1 2900cm when the following is used as the baseline -1 More than 2920cm -1 The maximum height of the following area was set as the reference peak height. -1 More than 1520cm -1 1280cm when the following is used as the baseline -1 Over 1295cm -1 The maximum height of the following region was divided by the reference peak height. This value was taken as the degree of crosslinking.

[0100] Crosslinking degree=(1280cm -1 Over 1295cm -1 (height of maximum value below) / (reference peak height) The above-mentioned method for measuring the degree of crosslinking was carried out three times, and the average value was calculated.

[0101] (3) Luminosity-corrected single transmittance and luminosity-corrected polarization degree Linearly polarized light from a prism was incident on the polarizer, and measurements were made using a spectrophotometer with an integrating sphere (V7100, manufactured by JASCO Corporation). MD transmittance and TD transmittance were obtained in the wavelength range of 380 nm to 780 nm, and the single transmittance and degree of polarization at each wavelength were calculated based on the following formulas (A) and (B). Furthermore, luminosity correction was performed using a 2-degree visual field (C light source) according to JIS Z 8701, and the luminosity-corrected single transmittance (Ty) and luminosity-corrected degree of polarization (Py) were obtained. The "MD transmittance" is the transmittance when the direction of the polarized light coming out of the Glan-Thompson prism is parallel to the transmission axis of the polarizing plate sample. In formulas (A) and (B), the "MD transmittance" is represented as "MD". The "TD transmittance" is the transmittance when the direction of the polarized light coming out of the Glan-Thompson prism is perpendicular to the transmission axis of the polarizing plate sample. In the formulas (A) and (B), "TD transmittance" is represented as "TD."

[0102] Visibility corrected single transmittance (%) = (MD + TD) / 2…(A) Visibility correction polarization degree (%)={(MD-TD) / (MD+TD)}×100…(B) (4) Adhesion A test piece having a width of 25 mm and a length of about 170 mm was cut out from the polarizing plate obtained in each Example and Comparative Example. Using a tensile tester (AUTOGRAPH AGX-50NX tester manufactured by Shimadzu Corporation), one end of the test piece in the length direction was gripped, and a 180° peel test was performed in accordance with JIS K 6854-2: "Adhesives - Peel Adhesion Strength Test Method - Part 2: 180° Peel" at a temperature of 23°C and a relative humidity of 60% at a crosshead speed (grip moving speed) of 300 mm / min. The peel force when peeling the first protective film 13a from the test piece was measured. The peel force when peeling the first protective film 13a was taken as the adhesion force.

[0103] <Examples and Comparative Examples> (Preparation of Polarizer A) A long polyvinyl alcohol film (average polymerization degree: approximately 2400, saponification degree: 99.9 mol % or more, thickness: 60 μm) was continuously transported and immersed in a swelling bath of pure water at 30°C for a residence time of 50 seconds (swelling process).

[0104] Next, the film was pulled out of the swelling bath and immersed in a dye bath containing iodine and potassium iodide / water at a mass ratio of 2 / 100 at 30° C. for a residence time of 60 seconds (dyeing step). Next, the film was pulled out from the dye bath and immersed in a first crosslinking bath containing potassium iodide / boric acid / water in a ratio of 12 / 3.0 / 100 (by mass) at 56° C. for a residence time of 40 seconds (first crosslinking step).

[0105] Next, the substrate was immersed in a second crosslinking bath containing potassium iodide / boric acid / water in a mass ratio of 8.9 / 2.49 / 100 at 40° C. for a residence time of 6 seconds (second crosslinking step). In the dyeing step, the first crosslinking step, and the second crosslinking step, the film was uniaxially stretched longitudinally by stretching between rolls in a bath (stretching step). The total stretching ratio based on the original film was 6 times.

[0106] Next, the film was pulled out from the crosslinking bath and immersed in a washing bath of pure water at 5° C. for a residence time of 1 second (washing step). The film was dried in a drying oven at 78° C. for a residence time of 100 seconds to obtain a polarizer A (drying step).

[0107] The thickness of the polarizer A thus obtained was 24 μm. The degree of boric acid crosslinking of the polarizer A thus obtained was measured and found to be 3.12. (Preparation of Polarizer B) A long polyvinyl alcohol film (average polymerization degree: approximately 2400, saponification degree: 99.9 mol % or more, thickness: 60 μm) was continuously transported and immersed in a swelling bath of pure water at 30°C for a residence time of 50 seconds (swelling process).

[0108] Next, the film was pulled out of the swelling bath and immersed in a dye bath containing iodine and potassium iodide / water at a mass ratio of 2 / 100 at 30° C. for a residence time of 60 seconds (dyeing step). Next, the film was pulled out from the dye bath and immersed in a first crosslinking bath containing potassium iodide / boric acid / water in a ratio of 12 / 4.1 / 100 (by mass) at 58° C. for a residence time of 40 seconds (first crosslinking step).

[0109] Next, the resultant was immersed in a second crosslinking bath containing potassium iodide / boric acid / water in a mass ratio of 8.49 / 2.49 / 100 at 40° C. for a residence time of 6 seconds (second crosslinking step). In the dyeing step, the first crosslinking step, and the second crosslinking step, the film was uniaxially stretched longitudinally by stretching between rolls in a bath (stretching step). The total stretching ratio based on the original film was 6 times.

[0110] Next, the film was pulled out from the second crosslinking bath and immersed in a washing bath of pure water at 5° C. for a residence time of 1 second (washing step). The film was dried in a drying oven at 78° C. for a residence time of 100 seconds to obtain a polarizer B (drying step).

[0111] The thickness of the polarizer B thus obtained was 24 μm. The degree of boric acid crosslinking of the polarizer B thus obtained was measured and found to be 3.45. (Preparation of Polarizer C) A long polyvinyl alcohol film (average polymerization degree: approximately 2400, saponification degree: 99.9 mol % or more, thickness: 60 μm) was continuously transported and immersed in a swelling bath of pure water at 30°C for a residence time of 50 seconds (swelling process).

[0112] Thereafter, the film was pulled out of the swelling bath and immersed in a dye bath containing iodine and potassium iodide / water at a mass ratio of 2 / 100 at 30° C. for a residence time of 60 seconds (dyeing step). Next, the film was pulled out from the dye bath and immersed in a first crosslinking bath containing potassium iodide / boric acid / water in a ratio of 12 / 3.9 / 100 (by mass) at 57.5° C. for a residence time of 40 seconds (first crosslinking step).

[0113] Next, the substrate was immersed in a second crosslinking bath containing potassium iodide / boric acid / water in a mass ratio of 9.0 / 3.5 / 100 at 40° C. for a residence time of 6 seconds (second crosslinking step). In the dyeing step, the first crosslinking step, and the second crosslinking step, the film was uniaxially stretched longitudinally by stretching between rolls in a bath (stretching step). The total stretching ratio based on the original film was 6 times.

[0114] Next, the film was pulled out from the second crosslinking bath and immersed in a washing bath of pure water at 5° C. for a residence time of 1 second (washing step). The film was dried in a drying oven at 78° C. for a residence time of 100 seconds to obtain a polarizer C (drying step).

[0115] The thus obtained polarizer C had a thickness of 24 μm and a degree of boric acid crosslinking of 3.58. <Preparation of active energy ray curable adhesive> The following cationic curable components were mixed to prepare an ultraviolet curable adhesive, which is an active energy ray curable adhesive.

[0116] 3',4'-Epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate (product name: CEL2021P, manufactured by Daicel Corporation): 70 parts by mass Neopentyl glycol diglycidyl ether (product name: EX-211, manufactured by Nagase ChemteX Corporation): 20 parts by mass 2-Ethylhexyl glycidyl ether (product name: EX-121, manufactured by Nagase ChemteX Corporation): 10 parts by mass Cationic polymerization initiator (product name: CPI-100, 50% solution, manufactured by San-Apro Co., Ltd.): 4.5 parts by mass (actual solid content 2.25 parts by mass) <Preparing the protective film> The following two types of protective films were prepared.

[0117] (First protective film) The first protective film is a 45 μm thick matte hard-coated triacetyl cellulose film manufactured by Dai Nippon Printing Co., Ltd. under the trade name "AGSR 16H."

[0118] (Second protective film) The second protective film is a 50 μm thick cyclic polyolefin resin film "ZB12" (product name) manufactured by Zeon Corporation.

[0119] <Preparation of polarizing plate> Example 1 1, a corona treatment was performed on the surface of the first protective film 13a that had not been subjected to the matte hard coat treatment and on the surface of the second protective film 13b. An ultraviolet-curable adhesive was applied to the corona-treated surfaces of the first protective film 13a and the second protective film 13b, and the films were attached to both sides of the polarizer A.

[0120] By the above procedure, a laminate consisting of first protective film 13a / ultraviolet-curing adhesive / polarizer 11 / ultraviolet-curing adhesive / second protective film 13b was produced. Next, an ultraviolet ray irradiation device with a belt conveyor (using a "D bulb" manufactured by Fusion UV Systems) was used to irradiate the second protective film 13b with an integrated light amount of 250 mJ / cm 2 . 2 Thus, a polarizing plate 10 having an adhesive layer 12 in which the ultraviolet-curable adhesive was cured was obtained. The thickness of the adhesive layer 12 was 3 μm.

[0121] The surface of the second protective film 13b of the polarizing plate 10 was subjected to a corona treatment, and a 25 μm-thick adhesive (product name "P-3132" manufactured by Lintec Corporation) was attached thereto to produce a polarizing plate with an adhesive layer.

[0122] The thus-prepared polarizing plate 10 with the adhesive layer was cut to a size of 200 mm x 25 mm with the absorption axis direction of the polarizer as the long side, and the polarizing plate 10 was attached to soda glass. Furthermore, the portion between the first protective film 13a and the polarizer 11 was partially peeled off with a cutter to prepare an adhesion evaluation sample. The adhesion evaluation sample was used to measure the adhesion by the above-mentioned method.

[0123] Comparative Example 1 A polarizing plate 10 with a pressure-sensitive adhesive layer was obtained in the same manner as in Example 1, except that polarizer B was used instead of polarizer A, and the adhesion strength was measured.

[0124] Comparative Example 2 A polarizing plate 10 with a pressure-sensitive adhesive layer was obtained in the same manner as in Example 1, except that polarizer C was used instead of polarizer A, and the adhesion was measured.

[0125] [Table 1]

[0126] As seen from Table 1, the polarizing plates prepared using the polarizers B and C of Comparative Examples 1 and 2 had adhesion strengths of 0.36 N / 25 mm and 0.34 N / 25 mm. In contrast, the polarizing plate prepared using the polarizer A of Example 1 had adhesion strength of 0.54 N / 25 mm, confirming that the adhesion strength between the polarizer and the protective film was improved. [Explanation of symbols]

[0127] 10...Polarizing plate 11...Polarizer 12…Adhesive layer 13…Protection film 13a...First protective film 13b…Second protective film 14…Swelling bath 15…Dyeing bath 16a…first crosslinking bath 16b…Second crosslinking bath 17...Complementary color bath 18…Cleaning bath 19...Drying oven 20…Polarizer manufacturing equipment 21…Original film 22...Roll 30~52,60,61...Guide roll 70~77…Nip roll

Claims

1. A polarizer in which a dichroic dye is adsorbed and oriented on a polyvinyl alcohol-based resin film, The degree of boric acid crosslinking is 3.3 or less; The visibility-corrected single transmittance is 40% or more, A polarizer having a luminous efficiency corrected polarization degree of 99.98% or more.

2. A polarizing plate comprising the polarizer according to claim 1 and a protective film on at least one surface of the polarizer.

3. Further, the polarizer and the protective film are bonded to each other by an attachment layer, The polarizing plate according to claim 2 , wherein the attachment layer is a layer formed by curing an active energy ray-curable adhesive.

4. A method for producing a polarizer in which a dichroic dye is adsorbed and oriented on a polyvinyl alcohol-based resin film, comprising the steps of: A dyeing step of dyeing the polyvinyl alcohol-based resin film with a dichroic dye; a crosslinking step of crosslinking the polyvinyl alcohol-based resin film that has been subjected to the dyeing step; A drying step of drying the polyvinyl alcohol-based resin film that has been subjected to the crosslinking step, The crosslinking step includes a first crosslinking step of immersing a polyvinyl alcohol-based resin film in a first crosslinking bath having a boric acid content of 4.0 parts by mass or less per 100 parts by mass of water; a second crosslinking step of immersing the polyvinyl alcohol-based resin film that has been subjected to the first crosslinking step in a second crosslinking bath having a boric acid content of 3.5 parts by mass or less per 100 parts by mass of water.

5. The method for producing a polarizer according to claim 4 , wherein the temperature of the first crosslinking bath is 60° C. or less, and the temperature of the second crosslinking bath is 45° C. or less.

6. A step of producing a polarizer by the production method according to claim 4 or 5; and a lamination step of laminating a protective film to one or both surfaces of the polarizer via an adhesive layer.

Citation Information

Patent Citations

  • Method of manufacturing polarizing film, and manufacturing device

    JP2022136978A